1996
DOI: 10.2307/1131712
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Perceived Daily Social and Academic Failure Experiences on School-Age Children's Subsequent Interactions with Parents

Abstract: The hypothesis that perceived failure experiences at school would increase the likelihood of aversive parent-child interactions after school was supported in a study of 167 fourth, fifth, and sixth graders. Children completed measures of mood, school events, and parent-child interaction 3 times each day for 2 consecutive days. Reports of social and academic failure experiences at school (e.g., peer problems and difficulty with schoolwork) were associated with increases in child self-reports of demanding and av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 42 publications
6
47
1
1
Order By: Relevance
“…For adolescents, academic failure has many negative consequences, ranging from strained parent-adolescent relations in the short-term (Repetti 1996) to truncated educational attainment 5 We reran these analyses using multi-level modeling, which corrects for the error structures that arise from cross-level interactions, such as those between individual-and school-level characteristics. When examining a dichotomous outcome variable, such as course failure, multi-level modeling techniques must be adjusted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For adolescents, academic failure has many negative consequences, ranging from strained parent-adolescent relations in the short-term (Repetti 1996) to truncated educational attainment 5 We reran these analyses using multi-level modeling, which corrects for the error structures that arise from cross-level interactions, such as those between individual-and school-level characteristics. When examining a dichotomous outcome variable, such as course failure, multi-level modeling techniques must be adjusted.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of these policies has broadened the consequences of academic failure beyond the student to stimulate greater interest among schools and teachers in students academic outcomes (Schiller and Muller 2003). Finally, beyond the school level, poor academic performance can strain significant relationships, such as parent-adolescent ties (Repetti 1996).The consequences of academic failure are not confined to adolescence or the actual period of formal schooling. Failure is an early indicator of potential dropout (Barrington and Hendricks 1989;Roderick 1993), linking this behavior to larger patterns of social inequality.…”
mentioning
confidence: 99%
“…In fact, in a different sample, Repetti (1996) found that children tended to report peer problems and academic problems on the same day. Thus, it is possible that some children regularly experience many stressful school events and that the psychological impact of these experiences may be equivalent.…”
Section: Peer Problems and Psychological Distressmentioning
confidence: 93%
“…All but one of the measures were taken from the Youth Everyday Social Interaction and Mood (YES I AM) scales (Repetti, 1996;Repetti & Wood, 2000). Mood and school events were assessed using the YES I AM scales.…”
Section: Methodsmentioning
confidence: 99%
“…Results of the study, based on child reports, suggested a circular negative process in which academic failure experienced by the child at school increased the probability of child perceptions of parent disapproval at home later in the day, which, in turn, increased the child's propensity to perceive rejections and failures at school the following day (Repetti, 1996). The results of this study are provocative.…”
Section: School Effects On Children and Familiesmentioning
confidence: 63%